The Objective Attitude in Architectural Academic Local Research (Arabic Paper) - Al-Dahwi, Suha Hassan; Rzqoo, Nawfal Joseph; Al-Wahab, Khalid Abd (Al-Nahrain Journal for Engineering Sciences, 2017)
Theory in general have been seen from two point of view, in one side, we find that Theory have drawn from the philosophical roots which have its consideration that consistence with people persuasion and researcher’s agreement, and from the other side theory is responsible about giving an interpretations and explanations about something in nature or in the cultural social world in a way that it’s statements may permit to be tested and analyzed by the action of the research. And because of the interdisciplinary wide range of subjects that may the theory of Architecture builds from , and in order to understand the scientific nature of the Academic Architectural local theorization, thereby we have to explain what do we mean by ( Theory) as a general Concept ,and in Architecture specifically ,in addition we have to explain the wide range of subjects that may the theory of Architecture builds from ,which makes its scientific testing method difficult because of the big parts of its subjects that belong to the human science where concepts like (Subjectivity),(Values),(Ideology) play a Big role in. and so the needs to provide a descriptive framework for the characteristics of the scientific theory in general was risen ,which may be very helpful to distinguish the instructions that achieve the scientific theory in its real meaning within the Academic Architectural local theorizing specifically. From here the research problem where determined by: " we do not have a framework that capable of describe the Academic Architectural local theorization whether it is achieve the criteria of formulating the scientific theorization or not. So the research seeks to:" state the nature of the scientific instructions to formulate the Architectural Theory , and the problem of it in general, and the way that we can classify the theory by, and disclose the theoretical framework which we can use to test the Architectural theorizing (postgraduate students dissertation - M.s.c. & Ph.D.- ) .the research determined the forward mechanism to achieve it’s Goal which consist of: defining the meaning of theory in general ,and the position of the Architectural theory in the Theorizing World to reach the characteristics of the general descriptive framework of theory to depend on in testing the Academic Architectural local theorization whether it is achieve its criteria or not. The research conclude that descriptive framework, and explain the interdisciplinary wide range of subjects that may the theory of Architecture builds from, and the way that the theory of Architecture were classified between (Normative &Positivist Theory) and the characteristics of each trend. The Research Findings were summarized that the Normative Theory ( the Argumentational theories especially) which work in (what Ought to be ) Level ,suffered from the difficulty of connecting them with the living world or with the fact the they cannot be tested, and the research also find that these theories by its Hypotheses do not have it’s logical connections ( we mean by logic :the relation between Premises & Conclusions),it’s Premises institutes on Metaphysical world beyond the real living world ) which work in (what Ought to be ) Level and the differences of their philosophical Structures due to the difference of their basic philosophical assumptions ( Existential , Epistemological ,Methodological ,and approach to the human nature) that adopted by the researchers. The research recommended the necessity of distinguish between the theorizing criteria for subject research that belong to the two level of hypotheses (what ought to be -level, & and the level of -what it is exist already) where it is not valid to conclude one from the other because they have different testing criteria.